Penambahan Ekstrak Daun Jambu Biji Daging Buah Merah (Psidium guajava var. pomifera) untuk Transportasi Ikan Mas (Cyprinus carpio) Sistem Basah - Ade Irawan; Mochamad Syaifudin; Mohamad Amin (Jurnal Akuakultur Rawa Indonesia, 2019)
The demand of live carp is higher and the price can be higher than the price of died carp. One of  ways to transport live fish was wet transportation system. The aim of this research was to know the effect of red guava leaf extract for reducing metabolism of common carp during transportation. This research used completely randomized design (CRD) with defferent concentration with four treatments and three replications i.e. of P. guajava var. pomifera leaves extract 0% (T0), 0.25% (T1), 0.50% (T2), and 0.75% (T3). The observed parameters were survival rate, glucose analysis and water quality (temperature, pH,  Dissolved Oxygen (DO), Total Ammonia Nitrogen (TAN) and carbon dioxide (CO2)). Addition of red fruit guava leave extract into transport media during transportation increased the percentage of survival rate of common carp during transportation. The survival rate of during transportation common carp was highest on T1, with the concentration of red fruit guava leave extract by 0.25%. The value of average in blood glucose levels was found in T2 (0.50%). Addition of P. guajava var. pomifera extract was able to reduce TAN values during transportation and the addition of P. guajava var. pomifera extract did not cause further effects on the survival rate of carp during maintenance post-transportation.